THE ROLE OF DIGITAL TECHNOLOGY IN ENHANCING PHYSICAL EDUCATION - Xoliqov Akmal Tojiddinovich (Ustozlar uchun, 2025)
This article explores the integration of digital tools and technology in physical education, emphasizing their positive impact on student engagement and learning outcomes. It discusses how technology, such as video feedback, fitness trackers, and anatomy apps, enhances students’ understanding of physical education topics like skill acquisition, biomechanics, and anatomy. The article highlights various case studies, including the use of video technology for individual instruction, peer video recording, and health-focused video projects. Additionally, it outlines the broader benefits of digital tools, such as increased student confidence, reduced stress, and improved study habits. The piece also acknowledges the challenges and costs of incorporating technology into PE, suggesting that schools can seek funding or grants to support these initiatives. The article concludes by reinforcing the value of technology as a powerful tool for enhancing physical education and encouraging students to take an active role in their health and fitness.